An enumeration of the orchidaceae of Central America, British Honduras and Panama - Williams, Louis O. (Zamorano: Escuela Agrícola Panamericana, 2016., 2016)
Una enumeración de la orchidaceae de Centroamérica, British Honduras y Panamá.